MAKNA â€œTUJUHâ€ DALAM TARI BEDHAYA DIRADHA META - Nur Rokhim (Greget, 2015)
TheBedhaya Dirada Metadance is performed by seven male dancersand is a symbol ofrespect to soldiers who have died in battle. The number seven in the Bedhaya Dirada Meta danceis closely related to the philosophy of Mankunegara I’s struggle. The basis of Mankunegara I’sstruggle in essence cannot be separated from the concept of leadership of the knights of Mataramwhich promotes three aspects, namely religion, morality, and culture. Of these three aspects, itsseems that the main philosophy used as a basis for Mankunegara I’s struggle is the concept ofreligious Islamic teachings in order to reach a level of perfection and to draw closer to God theCreator.Keywords: meaning, seven, bedhaya dirada meta.